Functional molecular expression of nature killer cells correlated to HBsAg clearance in HBeAg-positive chronic hepatitis B patients during PEG-IFN α-2a therapy - Cao, Weihua; Lu, Huihui; Zhang, Luxue; Wang, Shiyu; Deng, Wen; Jiang, Tingting; Lin, Yanjie; Yang, Liu; Bi, Xiaoyue; Lu, Yao; Zhang, Lu; Shen, Ge; et al. (Frontiers in Immunology, 2022)
Objective: To explore whether the frequencies and functional molecules expression of Natural Killer cells (NK cells) are related to hepatitis B surface antigen (HBsAg) disappearance in hepatitis B e envelope antigen (HBeAg)-positive patients with chronic hepatitis B (CHB) throughout peginterferon alpha-2a (PEG-IFN α-2a) treatment. Methods: In this prospective research, HBeAg-positive patients with CHB received PEG-IFN α-2a treatment, completing 4-year follow-up. After PEG-IFN α-2a treatment, undetectable HBV DNA, HBsAg loss, and HBeAg disappearance were defined as functional cure. Proportions of NK, CD56dim, CD56bright, NKp46+, NKp46dim, NKp46high, and interferon alpha receptor 2 (IFNAR2)+ NK cells, and the mean fluorescence intensity (MFI) of NK cell surface receptors IFNAR2 and NKp46 were detected. Results: 66 patients were enrolled into the study in which 17 patients obtained functional cure. At baseline, hepatitis B virus desoxyribose nucleic acid (HBV DNA) titer in patients with functional cure was remarkably lower than that in Non-functional cure group. Compared with baseline, HBV DNA levels, HBsAg levels, and HBeAg levels significantly declined at week 12 and 24 of therapy in patients with functional cure. At baseline, the negative correlation between CD56bright NK% and HBV DNA and the negative correlation between CD56dim NK% and HBV DNA was showed; CD56bright NK% and IFNAR2 MFI in patients with functional cure were remarkably higher than those in patients without functional cure. After therapy, CD56bright NK% and NKp46high NK% in patients with functional cure were higher than those in patients without functional cure. In Functional cure group, after 24 weeks of treatment NK%, CD56bright NK%, IFNAR2 MFI weakly increased, and NKp46high NK% and NKp46 MFI significantly increased, meanwhile, CD56dim NK% and NKp46dim NK% decreased. Only NKp46 MFI increased after therapy in patients without functional cure. Conclusion: The lower HBV DNA load and the higher CD56bright NK% before therapy, and the higher the post-treatment CD56bright NK%, IFNAR2 MFI, NKp46high NK%, the easier to achieve functional cure.